Immunoregulatory Effects of Stem Cell-Derived Extracellular Vesicles on Immune Cells - Xie, Min; Xiong, Wei; She, Zhou; Wen, Zaichi; Abdirahman, Amin Sheikh; Wan, Wuqing; Wen, Chuan (Frontiers in Immunology, 2020)
Recent investigations on the regulatory action of extracellular vesicles (EVs) on immune cells in vitro and in vivo have sparked interest on the subject. As commonly known, EVs are subcellular components secreted by a paracellular mechanism, and are essentially a group of nanoparticles containing exosomes, microvesicles, and apoptotic bodies. They are double-layer membrane-bound vesicles enriched with proteins, nucleic acids, and other active compounds. EVs are recognized as a novel apparatus for intercellular communication that act through delivery of signal molecules. EVs are secreted by almost all cell types, including stem/progenitor cells. The EVs derived from stem/progenitor cells are analogous to the parental cells and inhibit or enhance immune response. This review aims to provide its readers a comprehensive overview of the possible mechanisms underlying the immunomodulatory effects exerted by stem/progenitor cell-derived EVs upon natural killer (NK) cells, dendritic cells (DCs), monocytes/macrophages, microglia, T cells, and B cells.